Moral hazard: Experimental evidence from tenancy contracts - Burchardi, Konrad B; Gulesci, Selim; Lerva, Benedetta; Sulaiman, Munshi (Oxford Academic, 2022)
This article was published in The Quarterly Journal of Economics [©2018 Published by Oxford University Press] and the definite version is available at: https://doi.org/10.1093/qje/qjy023 The Article's website is at: https://academic.oup.com/qje/article/134/1/281/5106373